A Reconfigurable Optical Logic Gate With up to 25 Logic Functions Based on Polarization Modulation With Direct Detection - Xianfeng Tang; Zhongqin Fang; Yaxue Zhai; Xiangsen Jiao; Na Gao; Xiaoguang Zhang; Lixia Xi; Jianping Li; Wenbo Zhang (IEEE Photonics Journal, 2017)
We propose and investigate a new scheme to realize optical logic gates using polarization addition with direct detection. Two polarizations of an optical signal are modulated, respectively, by independent binary inputs to represent four different states, while direct detection is used to map the four states to the corresponding binary output. Up to 25 logic gates, including all the basic logic gates, can be implemented by adjusting bias voltages of the two modulators, peak–peak voltages of the driving signals, and the rotation angle between the two polarizations. A modified Poincare sphere and a simplified 2-D description are developed to illustrate the principle of the proposed scheme. Experiments are successfully carried out to realize all of the six basic logic gates at 1 Gb/s. Influences on the performance of logic gates are also studied by considering some key factors, such as the extinction ratio of Mach–Zehnder modulator (MZM), input power, and rotation-angle deviation.